Spectroscopic and antibacterial studies of new octaazamacrocyclic complexes derived from carbohydrazide and isatin - Kumar, Krishan; Kamboj, Monika; Jain, Kiran; Singh, D. P. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
A novel series of the macrocyclic complexes of the type: [M(C18H14N10O2)X-2], where M = Co(II), Ni(II), Cu(II) and Zn(II); X = Cl-, NO3- and CH3COO-, has been synthesized by template condensation of carbohydrazide and isatin in methanolic medium. The complexes were characterized by various physico-chemical techniques, such as elemental analyses, molar conductance measurements, magnetic measurements, and electronic, NMR, IR and EPR spectral studies. The low value of molar conductance indicates them to be non-electrolytes. Based on various studies, a distorted octahedral geometry was proposed for all the metal complexes. Metal complexes were tested for their in vitro antibacterial activities against some pathogenic bacterial strains and compared with standard antibiotic, Ciprofloxacin. Some of the tested complexes was found effective against Gram-positive bacterial strains. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbohydrazide; Isatin; Macrocyclic complexes; MIC; Template condensation